2018
DOI: 10.5603/ah.a2017.0024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentration of tryptophan and pregnancy-induced hypertension

Abstract: Introduction. Pregnancy-induced hypertension (PIH) is one of the main clinical problems of unexplained etiopathogenesis. New factors involved in the pathogenesis of this disease are still being searched. The available literature lacks data regarding the differences in tryptophan concentrations in physiological and PIH-complicated pregnancy. Previous studies have shown that L-tryptophan treatment reduces blood pressure in hypertensive rats. The direct vascular effects of tryptophan have not been fully explored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
4
1
Order By: Relevance
“…Though elevated Kyn, KA, and 5-HT as well as decreased MLT in PE-maternal serum have been reported [20,26,33,38], we do not detect significant differences in Kyn, KA, 5-HT, or MLT in either maternal or umbilical serum between NT and PE. However, we found that ILA was elevated in PEmaternal and umbilical vein sera.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Though elevated Kyn, KA, and 5-HT as well as decreased MLT in PE-maternal serum have been reported [20,26,33,38], we do not detect significant differences in Kyn, KA, 5-HT, or MLT in either maternal or umbilical serum between NT and PE. However, we found that ILA was elevated in PEmaternal and umbilical vein sera.…”
Section: Discussioncontrasting
confidence: 87%
“…Our observation that PE does not elevate Trp and Kyn in either maternal or fetal serum is consistent with the previous reports [25,33], in which PE did not change Trp and Kyn levels in maternal serum from the 2nd trimester of pregnancy [33], nor did PE alter Trp levels in umbilical serum from the 3rd trimester [25]. However, our observation contradicts the study by Grafka et al who demonstrated a 2.8-fold increase of Trp in PE-maternal serum from the 3rd trimester [20]. In addition, we do not find increases in KA and 5-HT, nor do we see a decrease in MLT in PE-maternal serum and increases in 5-HT and 5-HIAA in PE-umbilical vein serum [25].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Given the lower kynurenine concentration in women with PIH versus PE as identified through metabolomics, 48 and the similar concentration of kynurenine in PE and healthy women, it seems that women with PIH have both an increased tryptophan and a decreased kynurenine concentration. 49,50 These data thus suggest a decreased flux of tryptophan through the KP in maternal blood in PIH which differs from PE, and potentially represents an altered activity of other KP degrading enzymes, such as hepatic TDO2.…”
Section: Maternal Pregnancy Outcomesmentioning
confidence: 83%
“…Abbreviations: GC, gas chromatography; HPLC, high-performance liquid chromatography; IEx, Ion-exchange chromatography; KP, kynurenine pathway; LC, liquid chromatography; MS, mass spectrometry; MS/MS, tandem mass spectrometry; NM, not mentioned; UHPLC, ultra-high-performance liquid chromatography; UV, ultraviolet.van Zundert et al 11 studies, tryptophan was significantly higher in women with PIH compared to controls (QS = 5, mean (SD): 99 (7) vs 35 (9) µmol/L, N = 210, P < .00005) 49. However, in a smaller cohort study, this difference was not observed (QS = 4, mean (SD): 38.1 (10.3) vs 35.6 (9.5) µmol/L, N = 22).…”
mentioning
confidence: 95%